Geriatric assessment and biomarkers in patients with metastatic breast cancer receiving first-line mono-chemotherapy: Results from the randomized phase III PELICAN trial. Issue 2 (March 2018) - Honecker, Friedemann; Harbeck, Nadia; Schnabel, Claudia; Wedding, Ulrich; Waldenmaier, Dirk; Saupe, Steffen; Jäger, Elke; Schmidt, Marcus; Kreienberg, Rolf; Müller, Lothar; Otremba, Burkhard; Dorn, Julia; et al.
Abstract: Objectives: To determine predictive/prognostic factors for patients with metastatic breast cancer (MBC) receiving first-line monochemotherapy using biomarker analysis and geriatric assessment (GA). Materials and Methods: Karnofsky Performance Status (KPS) and GA as clinical parameters, and prognostic inflammatory and nutritional index (PINI), and Glasgow prognostic score (GPS) as biomarkers were analyzed for association with clinical outcome within the randomized phase III PEg-LIposomal Doxorubicin vs. CApecitabin iN MBC (PELICAN) trial of first-line pegylated liposomal doxorubicin (PLD) or capecitabine. Results: Of 210 patients, 38% were > 65 years old. GA (n = 152) classified 74% as fit, 10% as compromised, and 16% as frail. Biomarkers showed no age dependency. In multivariate analysis (n = 70) KPS, GA, cumulative illness rating scale-geriatrics (CIRS-G), and GPS were significantly associated with time to progression, and KPS, CIRS-G, and instrumental activities of daily living (IADL) from GA, and PINI showed a significant correlation with overall survival. Conclusion: GA evaluation was feasible. KPS significantly correlated with efficacy outcomes. Items of a GA and biomarkers of inflammation and nutrition may have prognostic significance in patients with MBC.